Tuberculosis-associated mortality and risk factors for HIV-infected population in Ethiopia: a systematic review and meta-analysis - Bizuneh, Fassikaw Kebede; Bizuneh, Tsehay Kebede; Masresha, Seteamlak Adane; Kidie, Atitegeb Abera; Arage, Mulugeta Wodaje; Sirage, Nurye; Abate, Biruk Beletew (Frontiers in Public Health, 2024)
Background; Despite the effectiveness of antiretroviral therapy in reducing mortality from opportunistic infections among people living with HIV (PLHIV), tuberculosis (TB) continues to be a significant cause of death, accounting for over one-third of all deaths in this population. In Ethiopia, there is a lack of comprehensive and aggregated data on a national level for TB-related mortality during co-infection with HIV. Therefore, this systematic review and meta-analysis aimed to estimate TB-associated mortality and identify risk factors for PLHIV in Ethiopia.